Pengujian Berbagai Tipe Tanam Jajar Legowo terhadap Hasil Padi Sawah - Sari, Dia Novita; Sumardi, Sumardi; Suprijono, Eko (Akta Agrosia, 2014)
Planting wetland paddy by setting row space could be a method to increase rice production. Legowo system is row planting method where we are able to apply different row types on paddy field. The objective ofthis research was to identify the best row planting type of ‘Jajar Legowo’ on growth and yield of wetland paddy. Six row plantings, including 2:1 type (means 2 rows are splited by wide space/ legowo), 3:1 type, 4:1 type, 5:1type, 6:1 type, and 7:1 typ, were tested in a Randomized Complete Block Design with 3 replications Results of the experiment revealed that the highest growth and yield as showed by total number of tillers (28), number ofproductive tillers (25), dry-mill rice (66.16 g per plant), and yield difference of dry-mill rice (50.43% per plot) was found at row planting type 2:1. Therefore, row planting type 2:1 can be selected as the best row.